Mapping Sustainable Development Goals (SDGs) Research Landscape in Indonesia: A Bibliometric Analysis - Farida, Wiwik Mukholafatul; Iqbal, Achmad; Iswahyudi, M. (Jurnal Pendidikan Akuntansi & Keuangan, 2024)
Sustainable Development Goals (SDG's) is a global issue and has become the target of various country leaders, including Indonesia. Sustainable Development Goals has become a research topic that continues to increase since 2016 in Indonesia. As a developing country, Indonesia has complex challenges in achieving sustainable development. This study aims to see how research conducted by academics, researchers, and practitioners in Indonesia has contributed to the achievement of these sustainable development goals. Bibliometric analysis was used to achieve the research objectives through descriptive analysis and network analysis. Data analysis includes descriptive analysis and network analysis. The results showed that the trend of SDG's research in Indonesia continued to increase from 2016 to 2024. The results also show that some research themes related to SDG's in Indonesia need greater attention related to themes such as Jakarta, water management, water supply, biodiversity, deforestation, and livehood. This is because research related to SDGs in Indonesia is still centred on the realm of government.